All-optical multiwavelength fiber lasers based on stimulated brillouin scattering - Abd. Rahman, Zubaidah (2011)
This thesis focuses on Multiwavelength comb generation in Fiber Lasers based on nonlinear effect in fiber optics named Stimulated Brillouin Scattering (SBS). The study had been carried out both in the linear cavity fiber laser and ring cavity fiber laser. A 5 km single mode fiber (SMF-28) was used as a Brillouin gain medium in the linear cavity of Brillouin/Erbium Fiber Laser (BEFL) incorporating a Tunable Bandpass Filter (TBF). A filter is recently used as a solution for having wider tunability of multiwavelength BEFL (MWBEFL) by suppressing the unwanted cavity mode and allowing the oscillation mode to be occurred at selected band. The exact location of Brillouin Pump (BP) wavelength to take place in order to have the optimum number of channel had been thoroughly studied. However, this technique has the limitation in the number of channel generated which depends on the filter bandwidth as well as the multiwavelength BEFL tunability that depends on the tunability of the filter. Two structures of ring cavity Fiber Lasers utilizing 11 km Dispersion Compensation Fiber (DCF) as the Brillouin gain medium which had been successfully demonstrated recently were improved by the development and improvement of the amplifier block as intended in this research work. Three different types of amplifier structures were demonstrated and the performance of each structure was studied. The conventional amplifier structure which consists of 8 m Erbium Doped Fiber (EDF) but pumped with 975 nm at maximum power of 616 mW, came out as the ideal pumping scheme to be used in this research work. The issue of low number of channel in a MWBEFL with a concept of virtual mirror which had been successfully demonstrated with an achievement of wide tunability of the entire Conventional-band (C-band) that only limited by the amplification area was successful resolved. Up to 9 laser lines were observed by utilizing the newly proposed pumping scheme. Another technique of having wide tuning range is the enhanced reverse-S-shaped BEFL. By using a pre-amplification technique, 10 laser lines was reported with the maximum output power of 20 mW. The issue of narrow tuning range which is only 14.8 nm tunability achieved from this structure was also successfully resolved with a new structure design. The ratio of the output signal that coupled to the Optical Spectrum Analyzer (OSA) was investigated beforehand. A series of experiment were carried out to find out the optimum output coupling ratio by varying the ratio of the variable coupler from 5% to 80%. The output power, number of channels and tuning range of each coupling ratio were recorded. The optimum output coupling ratio was found to be 10% which was measured based on the number of output channel and its tunability. As a result, 44 nm wide of tuning range was achieved in the reverse-S-shaped Multiwavelength Brillouin Fiber Laser (MWBFL) at 10% of output coupling ratio by utilizing the newly proposed pumping scheme. A 2 km of Highly Non-linear Fiber (HNLF) was also considered to replace the 11 km DCF as the Brillouin gain medium in the reverse-S-shaped structure. The performance of these two different fibers which act as the Brillouin gain medium was compared. HNLF was found to be a better Brillouin gain medium that managed to give 11 laser lines which can be tuned from 1520 nm to 1560 nm (40 nm) as compared to 11 km DCF.